Pemanfaatan Barang Milik Negara sebagai Dasar bagi Penerbitan Surat Berharga Syariah Negara Ditinjau dari Sistem Hukum Jaminan dan Sistem Hukum Kebendaan Nasional - Usman Arif Murtopo (Fakultas Hukum Universitas Islam Jember, 2014)
Term National Development Plan for 2005-2025 is a series of sustainable development efforts covering all aspects of society, nation and state. The series of the development effort includes development activities that take place endlessly, by raising the level of welfare of generation after generation. Implementation of the efforts made in the context of fulfilling the needs of the present without compromising the ability of future generations. One form of Islamic financial instruments which have been widely published both by corporate and state securities is based on sharia principles, or internationally known as Sukuk. Islamic financial instruments is different from the conventional securities. Another difference between the principle of securities based on sharia principles in exchange for not using the concept of interest as it is known in the international financial instruments.